World of chemistry - Joesten, Melvin D (Thomson Wadsworth, 2006)
14 subjects: Living in a world of Chemistry; the chemical view of matter; atoms; the periodic table; nuclear changes; chamical bonds: the ultimate glue; states of matter and solutions; chamical reactivity: chemmicals in action;...